THE LEGAL LIABILITY OF SELLERS IN SALE AND PURCHASE AGREEMENTS FOR NON-METALLIC ROCK MINERAL PRODUCTS - Siska Febriani; Annalisa Y (Fakultas Hukum Universitas Sriwijaya, 2026)
This research examines the legal protection aspects for buyers in sale and purchase agreements of non-metallic rock mining materials in Indonesia. Using normative juridical research methods with statute approach and conceptual approach, this study analyzes the applicable legal framework, implementation of supervision systems, dispute resolution mechanisms, and challenges in the era of transaction digitalization. The results show that the existing legal protection system has not provided adequate legal certainty for buyers, particularly in product quality verification and compensation procedures. Coordination between supervisory institutions remains weak, while standardization of contracts and transaction documentation is not yet optimal. The research recommends strengthening regulations through harmonization of rules, implementation of integrated digital verification systems, establishment of independent supervisory institutions, and development of more effective dispute resolution mechanisms. This research contributes to the development of a more comprehensive legal framework in protecting buyers' interests in non-metallic rock mining material transactions.